Vaping for weight control: A cross-sectional population study in England - Jackson, SE; Brown, J; Aveyard, P; Dobbie, F; Uny, I; West, R; Bauld, L (Elsevier, 2019)
Introduction Concern about weight gain is a barrier to smoking cessation. E-cigarettes may help quitters to control their weight through continued exposure to the appetite-suppressant effects of nicotine and behavioural aspects of vaping. This study explored the views and practices of smokers, ex-smokers and current e-cigarette users relating to vaping and weight control. Methods Cross-sectional survey of past-year smokers (n = 1320), current smokers (n = 1240) and current e-cigarette users (n = 394) in England, conducted April–July 2018. Data were weighted to match the English population on key sociodemographic characteristics. Results Of e-cigarette users, 4.6% (95%CI 2.6–6.6) reported vaping for weight control, and 1.9% (95%CI 0.6–3.2) reported vaping to replace meals/snacks. It was rare for individuals who had smoked in the past year to have heard (8.8%, 95%CI 7.3–10.3) or believe (6.4%, 95%CI 5.1–7.7) that vaping could help control weight. Women (OR = 0.62, 95%CI 0.42–0.93) and older people (OR = 0.30, 95%CI 0.13–0.72) were less likely to have heard the claim and women were less likely to believe it (OR = 0.44, 95%CI 0.27–0.72). However, 13.4% (95%CI 11.3–15.5) and 13.1% (95%CI 11.0–15.2) of current smokers who did not use e-cigarettes said they would be more likely to try e-cigarettes or quit smoking, respectively, if vaping could help control their weight. Conclusion One in 16 English people who have smoked in the last year believe that vaping would prevent weight gain after stopping. One in 22 people who vape are using e-cigarettes for this purpose. However, should evidence emerge that e-cigarettes prevent weight gain, one in eight people who smoke would be tempted to quit smoking and use e-cigarettes.